IMPLEMENTING MICROSOFT OFFICE 365 FOR INNOVATION ELT PRACTICES FACING COVID 19 - masofa, ima (Dinamika : Jurnal Sastra dan Budaya, 2020)
ABSTRACT: This study deals with teaching English by using Microsoft office 365 for innovation ELT Practices in Students in Junior High School in facing Corona 19. As one of the communicative skills, reading should be achieved by the student to be able understand English. Unfortunately, some students have difficulties to study English at school when Covid 19 spreads in Indonesia. Students have to stay at home to stay safe. Therefore, implementing Microsoft Office 365 for innovation ELT practices facing Covid 19 of students in eight grade of Junior High School are expected to increase students ‘ability to understand English about general truth. The objective of this study are to find out how the teacher implement Microsoft Office 365 and how the students’ ability to understand general truth by using Microsoft Office 365. The assessment of implementing Microsoft Office 365 for innovation ELT Practices in Students of Junior High School was analyzed by using Microsoft Office 365‘s scoring rubric which consists of analysis students’ answer. The results of this research can be formulated as follows: 1) Students can answer questions of general truth well based on Microsoft Office responses from students.2) Students’ scoring analysis to answer general truth is described Microsoft Office 365 that most students achieve 90 when they answered general truth questions that can be found in Microsoft Office 365 of students ‘response.